Critical lifting simulation of heavy industrial construction in gaming environment. Issue 1 (4th June 2020) - Sydora, Christoph; Lei, Zhen; Siu, Ming Fung Francis; Han, SangHyeok; Hermann, Ulrich
Abstract : Purpose: Heavy industrial construction often relies on large mobile cranes to erect equipment and pre-assembled modules. Engineering calculations are required for the lifting analysis where lifting capacity is analyzed to ensure the feasibility of the lifting scenarios. Such engineering calculations are often presented in static formats, e.g. two-dimensional or three-dimensional models. However, it is difficult to help practitioners (e.g. lifting engineers, site crews and operators) understand the complexity of the lifting process and thus operational decisions are often made intuitively. Therefore, this paper aims to introduce a game-based simulation system to allow for interactive analysis of the lifting process to improve lifting efficiency and safety. Design/methodology/approach: The proposed method treats the mobile crane as a robot with degree-of-freedoms, and the movements are simulated in the Unity game environment. The lifting capacity is calculated dynamically based on the lifting object weight, rigging weight and lifting radius. Findings: Compared with the four-dimensional visualization, this development has added a dimension of real-time interactive simulation; this allows the users to understand the complexity and feasibility of the lifting process. Originality/value: The developed prototype has been tested and validated using a real case study from a heavy industrial project with the possibility of generalizing crane lifting configurations.